Kemandirian Belajar Mahasiswa Keperawatan dalam Pembelajaran Daring di Era Pandemi Covid-19 - Christian Irmando Sikteubun; Evelyn Hemme Tambunan (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Self-directed learning is one of the professional values of nurses. Nurses are required to commit to lifelong learning. The professional value of self-directed learning must be developed from the educational stage, even in online learning in the Covid-19 pandemic era. The purpose of the study was to describe the level of self-directed learning of nursing students in online learning in the era of the Covid-19 pandemic. The research method used is quantitative descriptive, with the convenience sampling method. The research sample was undergraduate nursing students at the Faculty of Nursing, Adventist University of Indonesia. The number of samples was 153 respondents and the research time was June-December 2021. The research instrument used was a valid questionnaire, namely the nursing student self-directed learning questionnaire. Questionnaire data was collected using google form and the data were analyzed using a frequency distribution to determine the level of self-directed learning in the high, medium and low categories. The results showed that most of the respondents namely 112 respondents (73,2%) were at the moderate level of self-directed learning,, a small part, namely 20 respondents (13,1%) were at the high level of self-directed learning and 21 respondents (13,7%) are at a low level of self-directed learning. It is important to explore further the factors that influence the self-directed learning in online learning and educators may facilitate the increasing of self-directed learning of nursing students.